Dimensional analysis of burden in family caregivers of patients with obsessive-compulsive disorder - Torres, Albina Rodrigues [UNESP]; Hoff, Natalia Travenisk; Padovani, Carlos Roberto [UNESP]; de Abreu Ramos-Cerqueira, Ana Teresa [UNESP] (Wiley-Blackwell, 2012)
Aims: Obsessivecompulsive disorder (OCD) also generates emotional burden in the patient's family members, but no study has evaluated the specific dimensions of burden. The objectives were to evaluate the dimensions of the Zarit Burden Interview (ZBI) and possible correlates. Methods: This was a cross-sectional study involving 47 patients and 47 caregivers, using a sociodemographic questionnaire; the ZBI; the Self Reporting Questionnaire; the Family Accommodation Scale; and the YaleBrown ObsessiveCompulsive Scale. The ZBI factor analysis was conducted using Varimax Rotation. Results: Six factors were identified, explaining 74.2% of the total variance: factor 1, interference in the caregiver's personal life (36.6% of the variance); factor 2, perception of patient's dependence (10.8%); factor 3, feelings of irritation or intolerance (9.2%); factor 4, guilt (7.2%); factor 5, insecurity (5.6%); and factor 6, embarrassment (4.8%). The six ZBI factors were associated with greater OCD severity and with greater accommodation to the patient's symptoms, and factors 1, 2, 5 and 6 with caregiver's psychological morbidity. Caregiver's sex (female) was associated with factors 5 and 6, relationship with the patient (being a parent or son/daughter) with factor 5, higher educational level with factor 6, living with the patient with factor 3, worse self-evaluation of health with factors 1, 5 and 6, and occupational status (not working) with factors 1, 2, 5 and 6. Conclusion: The dimensions of burden identified indicate the most affected aspects of a caregiver's life and could guide the planning of more specific interventions. Thus, the caregiver could participate more effectively in the OCD patient's treatment, with a lower impact on his/her life.
Keywords: burden; caregiver; factor analysis; obsessive-compulsive disorder; Zarit Burden Interview